2008
DOI: 10.1016/j.trstmh.2008.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Understanding home-based neonatal care practice in rural southern Tanzania

Abstract: SummaryIn order to understand home-based neonatal care practices in rural Tanzania, with the aim of providing a basis for the development of strategies for improving neonatal survival, we conducted a qualitative study in southern Tanzania. In-depth interviews, focus group discussions and case studies were used through a network of female community-based informants in eight villages of Lindi Rural and Tandahimba districts. Data collection took place between March 2005 and April 2007. The results show that altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 49 publications
7
83
1
Order By: Relevance
“…Very similar results were also found in Bangladesh, Nepal, Pakistan and Tanzania (8,9). Interventions to improve newborn care must prioritize postnatal care, and take into account the local socio-cultural situation and barriers to accessing including the financial burden [10].…”
Section: Discussionsupporting
confidence: 62%
“…Very similar results were also found in Bangladesh, Nepal, Pakistan and Tanzania (8,9). Interventions to improve newborn care must prioritize postnatal care, and take into account the local socio-cultural situation and barriers to accessing including the financial burden [10].…”
Section: Discussionsupporting
confidence: 62%
“…Similar results have been found in Bangladesh, Pakistan, Nepal and Tanzania. [38][39][40] Recently, Owais et al 41 reported on care-seeking characteristics of families who have infants with possible serious bacterial infection in Pakistan. Factors associated with seeking care from skilled HCP included recognition by the mother of severity of illness, families able to speak the dominant language spoken in the hospital and the presence of fever or grunting in the child.…”
Section: Local Understandings Influence Treatment Practicesmentioning
confidence: 99%
“…Such forms of 'protection' include applying drugs, cow dung, and powder to help heal the cord. Bathing also plays a role here, and babies are bathed early, sometimes with cold water [32]. Studies in South Asia have reported similar findings, including unhygienic cord cutting and care, as well as early bathing [23,[33][34][35][36].…”
Section: Acceptability Of Evidence-based Newborn Care Practices At Comentioning
confidence: 77%